Médicaments génériques : pivot de la reconstruction de l’industrie pharmaceutique - Philippe Abecassis; Nathalie Coutinet (Revue de la Régulation)
The pharma has a particular significance given the challenges it involves for public health, economics, politics and ethics. The medicines production is therefore subject to multiple and complex regulations, both national and international. While some of these regulations was designed against major pharmaceutical companies (Big Pharma), firms have often co-constructed the regulation with the intent to take advantage. The analysis of the changing patterns of production and successive big pharma’s strategies can highlight the importance of the co-construction of regulation. This work shows how the “generic” model of medicines production which follows the “blockbusters” model appears as a transitional model, a pivot from which firms intend to escape as quick as possible, encouraged by the regulators, to find a “custombusters” model without its predecessor’s defects.